2009
DOI: 10.1111/j.1349-7006.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Core fucosylation of E‐cadherin enhances cell–cell adhesion in human colon carcinoma WiDr cells

Abstract: a1,6-Fucosyltransferase (Fut8), an enzyme that catalyzes the introduction of α1,6 core fucose to the innermost N-acetylglucosamine residue of the N-glycan, has been implicated in the development, immune system, and tumorigenesis. We found that α1,6-fucosyltransferase and E-cadherin expression levels are significantly elevated in primary colorectal cancer samples. Interestingly, low molecular weight population of E-cadherin appeared as well as normal sized E-cadherin in cancer samples. To investigate the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 52 publications
3
76
0
Order By: Relevance
“…This discrepancy can be due to the expression of E-cadherin, which is detected in Hep3B but not these aggressive lung cancer cell lines we used. E-cadherin is a calcium-dependent cell-cell adhesion molecule with a pivotal role in tumor suppression (30), and it has been reported that core fucosylation of E-cadherin can enhance cell-cell adhesion in human colon carcinoma cells (10). Therefore, overexpressing FUT8 in Hep3B cell, an epithelial-type cell, which is positive in E-cadherin expression, may strengthen Ecadherin-mediated cell-cell interaction and reduce the metastatic abilities of FUT8 transfectants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy can be due to the expression of E-cadherin, which is detected in Hep3B but not these aggressive lung cancer cell lines we used. E-cadherin is a calcium-dependent cell-cell adhesion molecule with a pivotal role in tumor suppression (30), and it has been reported that core fucosylation of E-cadherin can enhance cell-cell adhesion in human colon carcinoma cells (10). Therefore, overexpressing FUT8 in Hep3B cell, an epithelial-type cell, which is positive in E-cadherin expression, may strengthen Ecadherin-mediated cell-cell interaction and reduce the metastatic abilities of FUT8 transfectants.…”
Section: Discussionmentioning
confidence: 99%
“…Lacking the core fucose on these receptors leads to a marked reductions in ligand binding ability and downstream signaling. Furthermore, the increase in core fucosylation on E-cadherin has been shown to strengthen cell-cell adhesion (10).…”
mentioning
confidence: 99%
“…In fact, the expression of these determinants in epithelial cancer has been reported to correlate with the poor prognosis of human colon cancer (23). In addition, α1-6 fucosylation (core fucosylation) is crucial for the functions of several growth factor receptors, such as EGF (24) and TGF-β receptors (25), and adhesion molecules, such as integrins (26) and E-cadherin (27). Core fucosylation is very closely involved in the biological behavior of cancer cells through regulation of the functions of these membraneassociated receptors (28).…”
Section: Cancer and Fucosylationmentioning
confidence: 99%
“…Fucosylation involves the attachment of an L-fucose residue to an oligosaccharide or protein and is one of the most important oligosaccharide modifications in cancer (13). Most cell surface receptors, including epidermal growth factor receptor (14), transforming growth factor-␤ receptor (15), E-cadherin (16), and integrins (17), are fucosylated. Fucosylated oligosaccharides regulate many physiological and pathological events, including cell growth, migration, embryogenesis, and tumor invasion, by affecting the folding and structure of these cell surface receptors (18).…”
Section: Tumor Necrosis Factor-related Apoptosis-inducing Ligand (Tramentioning
confidence: 99%